EFEKTIVITAS MODEL PEMBELAJARAN CPA BERBASIS MEDIA BLOK DIENES TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS III SDN 5 KESU’ - Fenny Paonganan; Novalia Sulastri; Reni Lolotandung (STKIP Subang, 2026)
Abstract This study aims to determine the effectiveness of the Concrete-Pictorial-Abstract (CPA) learning model based on Dienes Block media on the mathematical problem-solving ability of third-grade students at SDN 5 Kesu'. This research is a quantitative study with a pre-experimental design (one-group pretest-posttest design). The population as well as the sample of this study were all 24 third-grade students at SDN 5 Kesu', selected using the saturated sampling technique. The data collection instrument was a mathematical problem-solving ability test consisting of 18 valid and highly reliable essay items (a = 0.888). Data analysis techniques utilized descriptive and inferential statistics. The hypothesis testing using the paired sample t-test showed a significance value of Sig. (2-tailed) = 0.000 < 0.05, indicating a highly significant difference in the students' mathematical problem-solving abilities before (pretest) and after (posttest) the intervention. Thisimprovement is also supported by an average N-gain score of 0.51, which falls into the